7,8-Dihydroxyflavone induces mitochondrial apoptosis and down-regulates the expression of ganglioside GD3 in malignant melanoma cells - Won Seok Ju; Sang Young Seo; Seong-eun Mun; Kyongtae Kim; Jin Ok Yu; Jae-Sung Ryu; Ji-Su Kim; Young-Kug Choo (Discover Oncology, 2023)
Abstract Malignant melanoma is a skin cancer with poor prognosis and high resistance to conventional treatment. 7,8-dihydroxyflavone (7,8-DHF) has shown anti-carcinogenic, anti-inflammatory, anti-oxidant, and pharmacological effects in several types of cancer. However, the relationship between ganglioside expression and the anti-cancer effects of 7,8-DHF in melanoma is not fully understood. In the present study, 7,8-DHF exhibits specific anti-proliferation, anti-migration, and G2/M phase cell-cycle arrest effects on both melanoma cancer cell lines, and induces mitochondrial dysfunction and apoptosis, making it a potent candidate for anti-melanoma treatment. Furthermore, we confirmed that 7,8-DHF significantly reduces the expression levels of ganglioside GD3 and its synthase, which are known to be closely involved in carcinogenesis. Taken together, our findings suggest that 7,8-DHF may be a potent anti-cancer drug candidate for the treatment of malignant melanoma.